# (3q – r)(q + 2r). solve please?

... Please help me solve this.If a=x+y(3p-1) , b=x+y(3q-1) , c=x+y(3r-1) , find: i) the value of a(q-r)+b(r-p)+c(p-q) ii) prove that ... 3q)/(p-q) = (3q - 3r)/(q-r ... - Read more

2p +3q- 2r = 32 2p+3q -4r= 23-----p-2q + 3r= 7 --> p = 2q - 3r + 7 Sub ... That'll give 2 eqns in q & r solve 1 eqn for either, sub into the other eqn. ... - Read more

## (3q – r)(q + 2r). solve please? resources

### If px^2+qx+r=0, then sum of squares of roots it equal to....

... the sum of the squares of the roots is equal to sum of the cubes of the roots and q^3+pq^2=2p+3q ... r =0, the sum of the ... Please tell me how you think you ...

### Solutions 4

13.a) We have Q′ 1 = −2r V ... c2 = 3Q0/2. Hence we ﬁnd Q1 ... Q0 2 e−3τ = 0.01Q 0. We can solve this approximately by assuming that e−3 ...

### Cubic Diophantine Equations and Ramanujan

v 7 (6pqr) = –(p 3 +q 3-3q 2 r+3p 2 s)v 1 – (p 3 +q 3-3q 2 r-3p 2 s)v 3 . and for ... and one can easily solve for the v i with even subscripts as they are only ...

### Can someone solve math problems for me? - qfak.com

it's factorization mainly. please solve them all correctly but show how ... substitute q for (x - y) q(q - 3) + 2. q^2 - 3q + 2 ... 3.....x^2 + 2x = r. r^2 - 2r - 3 ...

### what is 2.3q-16=5q+38 - Math Homework Answers

... please log in or register. ... solve for q; 1 answer 61 views. ... given that s= 5q+4p/3 +2r, express p in terms of q,r and s. asked Jun 25, ...

### Ramanujan And The Cubic Equation 3 + 4 + 5 3 = 6 3 By ...

... as the form to solve, ... 2a = (1-(p-3q)(p +3q2))r b = ((p+3q)(p 2+3q )-1)r c = ((p ... /2, s = (a-b)/2, q = (c+d)/2 r = (-c+d)/2 The expressions f i in fact are ...

### Trouble with some profit, revenue, cost questions [Archive ...

[quote="conp"]Thanks for the response. You're welcome. Let's try one question at a time OK? I'm pretty sure total revenue is R(q)=P*Q. Absolutely correct, but please ...

### 007: Simultaneous Polynomials made squares - A Collection ...

... {pqrs, (p 2 +s 2)(q 2 +r 2)} are to be ... For Lenhart’s case, with {m,n} = {1, 4), one needs to solve p 2 +q 2 = 5 which ... (p-q)(p+3q)r, 2(p 2 +3q 2)s ...

### Physics: Engineering Science, vector cross product

p = 4i+ j – 2k, q = 3i – 2j + k and r = i ... x r (ii) p x (2r x 3q). can you please give me a Brief comment based on your answer. Answer First let me note that: ...

### Substitution - ThatQuiz

... Inequalities & their graphs Solve and graph ... q = 2, r = 3 and s ... (q - r + s) (f) r(2p - 3q) = = = (a) 2s(3p-2q) (b) pq + rs (c) 2pr - 3rq. If p=4, q = 2, r ...

### Answers To Math Problems: Long Math Problem

Many stiudents favorite and best website to solve long math problem is tutor vista. ... 3p + q + 2r = 11, 2p + 3q + r = 11. ... q = 2, r = 3. Long Math Problem

Question 40309: PLEASE HELP! ... "What is q when: tq-r=3q+p" any help will be appriciated. ... =r+p Solve for "q": q=(r+p)/(t-3) Cheers,

### Simplex Algorithm for Maximisation problem

Q + R + S 2 = 80 ... 3Q – 2R = 0, ... To solve equations and ensure that a value is obtained for them we must have equal number of equations and equal number of ...

### Static equilibrium for three point charges

I think this was the easiest problem we had to solve for charge distributions and point charges ... as 3q/L^2 and Q/r^2 are both ... 4Lr + 2r^2 = 3r^2 r^2 + 4Lr ...

### Simplex Algorithm for Maximisation problem

... Q + R ≤ 80. Q + R + S 2 = 80 ... To solve equations and ensure that a ... Thus if we look back at our objective function P = 3Q + 2R, and we substitute in Q and ...

### Simplify and solve this equation for q: 3q + 5 + 2q – 5 ...

Simplify and solve this equation for q: 3q + 5 + 2q ... What are the points? Please mention the points so I can find the slope. ... R. L. 1. 1. P. C. 1. P. 1. 1. L. P ...

### Basis of a subspace and dimension question

... (-1)t= p+ 2r- s- t= 0, b.x= (2)p+ (1)q+ (1 ... 4p+ 3q- r+ 5s+ 2t= 0 You can solve for three of the values in terms of ... (p, q, r, s, t)= (s- t, 2s+t, 3s ...

### A Charge 3q Is At The Origin, And A Charge -2q ... | Chegg.com

Q: q3 at ((r-a), 0) r: Distance from 3q to Q. a ... I already know I'm supposed to plug this into the quadratic formula and solve for ... Please and thanks! Best ...

### 010: Sum / Sums of Three Cubes, Part 1 - A Collection of ...

Expanding, we get p(p 2 +3q 2) = r(r 2 +3s 2). ... r-s√-b = (p-q√-b)(u-v√-b) Solve for {r,s}, ... x 3 +y 3 +2(z 3 +t 3) = (p 3 +q 3 +2(r 3 +s 3)) ...

### BASIC ALGEBRA I - Caresa

... 6q + 18 + 3q = 3 – q . Q.7. An apricot costs 10 cents more than a peach. ... Q.2. Simplify: (a ... (f) (r + 2)(r 2 – 2r + 4) (g) (3pq + r)(2pq – r) Q.5.

### A Static Solution of Proca Equat - Uprh

... 4πρ(r) . We will solve (1) ... (r) = q /{ (4π/3) R 3} , ... (2R 3))r 2 + 3q/(2R) , r ≤ R , (4) ...

Related Questions

Recent Questions